(untitled) (Bangladesh Pharmaceutical Journal, 2026)
This study sought to comprehensively explore the thrombolytic and membrane-stabilizing activities of allyl isothiocyanate (AITC) through both in vitro experimental assays and computational analysis. To investigate its thrombolytic activity, we conducted clot-lysis assays that mimic physiological clot formation and breakdown. In parallel, the membrane-stabilizing activity of AITC was assessed via human erythrocyte hemolysis assays, designed to cellular membrane damage that occurs during inflammation and oxidative stress. These assays allowed us to investigate the therapeutic relevance of AITC in conditions involving thrombosis and cell lysis. Additionally, molecular docking studies made us understand the potential interactions of AITC with two key molecular targets: plasminogen, which contributes significantly to the breakdown of fibrin clots, and cyclooxygenase-1 (COX-1), a major enzyme involved in the inflammatory responses. The in vitro results showed that AITC exerted concentration-dependent effects. At 100 μg/ml concentration, AITC achieved 82.18 ± 0.01% clot dissolution and 92.10 ± 0.01% membrane protection. The IC₅₀ values were observed to be 41.70 ± 1.47 μg/ml for clot-lysis and 36.01 ± 1.71 μg/ml for membrane-stabilization, indicating potent bioactivity. Docking analysis demonstrated favorable interaction of AITC with plasminogen (−4.2 kcal/mol) and COX-1 (-4.5 kcal/mol), suggesting possible mechanisms underlying its observed effects. Taken together, these results suggest that AITC may function through dual fibrinolytic and anti-inflammatory pathways. Its ability to interact with key proteins involved in clot resolution and inflammation suggests it as a promising natural therapeutic candidate. However, additional clinical and pre-clinical investigations are required to establish its therapeutic safety and efficacy profile. Bangladesh Pharmaceutical Journal 29(1): 53-67, 2026 (January)